DEVELOPMENT AND TESTING OF A POLYCARBONATE-COATED SOLAR INSTALLATION FOR DRYING AGRICULTURAL PRODUCTS (World Science, 2021)
The proposed solar drying system significantly reduces the drying time and improves the quality of the product, including the preservation of vitamins. When drying rosehip, a laboratory analysis for vitamin "C" showed that 28% of this vitamin is destroyed during natural drying, and 17% when using a solar dryer.The drying speed increases by 2.5 - 4 times compared to traditional outdoor drying.In the proposed installation, you can dry different agricultural products, you can change the coating of the solar drying unit. In S/D, the air temperature is higher than in the environment from about 13 to 32 degrees Celsius, depending on weather conditions.The drying process in the S/D apparatus allows you to ensure the purity of the products. S/D is covered and during the drying process the product is not contaminated with dust and rain, by influence of dew, is not damaged by birds, insects or wasps.This device is convenient for transportation, during the day it can be moved and rotated to align to the sun.The proposed solar dryer is easy to manufacture and can be widely used in large and small farms, private and subsidiary farms.